Analyzing the effectiveness and safety of arthroscopic suture anchor repair for anterior talofibular ligament in patients with ankle instability - Zhaole Xu; Qian Li; Xuan Ding; Yiqiong Nie; Ning Chen (PLoS ONE, 2025)
Background Ankle instability, often secondary to anterior talofibular ligament (ATFL) injury, poses significant challenges in orthopedic management. This study aimed to evaluate the effectiveness and safety of arthroscopic suture anchor repair for ATFL in patients with ankle instability. Methods This retrospective study spanned from January 2022 to February 2024 and involved 58 patients who underwent arthroscopic repair and 60 patients who underwent the open Broström procedure. Baseline characteristics, surgical outcomes, and functional assessments utilizing the Ankle Hindfoot Scale (AOFAS) were compared between the two groups. Additionally, talar tilt angle and anterior translation distance were measured using anteroposterior and lateral ankle radiographs. Results Both groups showed significant improvements in AOFAS scores post-treatment (p < 0.001). The observation group had shorter surgical durations, reduced blood loss, and quicker recovery times compared to the control group (p < 0.001). Talus tilt angle and anterior translation distance decreased significantly in both groups postoperatively (p < 0.001). Arthroscopic repair demonstrated superior outcomes in terms of AOFAS scores and surgical parameters. Conclusions Arthroscopic suture anchor repair is an effective and safe option for managing ankle instability, offering procedural efficiency, reduced blood loss, and favorable functional outcomes. Further research is needed to validate these findings and compare arthroscopic techniques with conventional open procedures.